Clinical Characteristics of Basilar‐Type Migraine in the Neurological Clinic of a University Hospital. Issue 7 (25th March 2014) - Ying, Guomin; Fan, Wen; Li, Nan; Wang, Jing; Li, Wangwen; Tan, Ge; Zhou, Jiying
Abstract Objectives The aim of this study was to investigate the prevalence and clinical characteristics of basilar‐type migraine in the neurology outpatient clinic of a university hospital in China. Methods This cross‐sectional study was conducted in the neurology outpatient of a tertiary care hospital in Chongqing between January 2010 and December 2011. All consecutive patients citing headache as their chief complaint were asked to complete a face‐to‐face interview by a qualified headache specialist using a detailed questionnaire for headache. The diagnosis of basilar‐type migraine was made according to International Classification of Headache Disorders Second Edition. Results Of the 1, 526 headache patients, 23 (1.5%) were diagnosed with basilar‐type migraine (19 women, four men). Basilar‐type migraine occurred in 6.6% (23/348) of patients with migraine with nonhemiplegic aura. Mean age at onset was 20.3 ± 11.7 years (range 6–49 years). Among these patients, 65% (15/23) reported bilateral pain, 35% (8/23) unilateral pain. The basilar‐type aura comprised diplopia 52%, vertigo 43%, tinnitus 43%, bilateral visual symptoms 39%, hypacusia 26%, ataxia 26%, dysarthria 22%, bilateral paresthesias 13%, and decreased level of consciousness 13%. Intense emotional stimuli (74%) and sleep disorders (65%) were the most common trigger factors, followed by change in weather, sunshine, cold wind, acute stress, alcohol, and fatigue. Conclusion Basilar‐type migraine is an episodic disorder and occurred in 1.5% of patients with headache. More than one‐half of patients have their first attack in the second and third decade of life. Trigger factors were common, and patients should be educated to avoid trigger factors.